Analgesic Effect of Coptis chinensis rhizomes (Coptidis Rhizoma) Extract on Rat Model of Irritable Bowel Syndrome - Tjong, Yungwui (2011)
AIM OF STUDY: Coptis chinensis rhizomes (Coptidis Rhizoma, CR), also known as “Huang Lian”, is a common component of traditional Chinese herbal formulae used for the relief of abdominal pain and diarrhea. Yet, the action mechanism of CR extract in the treatment of irritable bowel syndrome is unknown. Thus, the aim of our present study is to investigate the effect of CR extract on neonatal maternal separation (NMS)-induced visceral hyperalgesia in rats and its underlying action mechanisms. MATERIALS AND METHODS: Male Sprague-Dawley rats were subjected to 3-hr daily maternal separation from postnatal day 2 to day 21 to form the NMS group. The control group consists of unseparated normal (N) rats. From day 60, rats were administrated CR (0.3, 0.8 and 1.3 g/Kg) or Vehicle (Veh; 0.5% carboxymethylcellulose solution) orally for 7 days for the test and control groups, respectively. RESULTS: Electromyogram (EMG) signals in response to colonic distension were measured with the NMS rats showing lower pain threshold and increased EMG activity than those of the unseparated (N) rats. CR dose-dependently increased pain threshold response and attenuated EMG activity in the NMS rats. An enzymatic immunoassay study showed that CR treatment significantly reduced the serotonin (5HT) concentration from the distal colon of NMS rats compared to the Veh (control) group. Real-time quantitative PCR and Western-blotting studies showed that CR treatment substantially reduced NMS induced cholecystokinin (CCK) expression compared with the Veh group. CONCLUSIONS: These results suggest that CR extract robustly reduces visceral pain that may be mediated via the mechanism of decreasing 5HT release and CCK expression in the distal colon of rats.